Metabolic syndrome and risk of stroke: Protocol for an update systematic review and meta-analysis. Issue 15 (April 2018) - Roever, Leonardo; Resende, Elmiro Santos; Diniz, Angélica Lemos Debs; Penha-Silva, Nilson; O'Connell, João Lucas; Gomes, Paulo Fernando Silva; Zanetti, Hugo Ribeiro; Roerver-Borges, Anaisa Silva; Veloso, Fernando César; Fidale, Thiago Montes; Casella-Filho, Antonio; Dourado, Paulo Magno Martins; et al.
Abstract: Introduction: The metabolic syndrome is composed of several cardiovascular risk factors and has a high prevalence throughout the world. However, there are no systematic analyses or well-conducted meta-analyses to evaluate the relationship between metabolic syndrome and stroke. The aim of this study is to examine this association of metabolic syndrome with stroke in different ages and sex. Methods and analysis: The update systematic review and meta-analysis will be conducted using published studies that will be identified from electronic databases (i.e., PubMed, EMBASE, Web of Science, and Google Scholar. Studies that examined the association between metabolic syndrome and stroke, had a longitudinal or prospective cohort design, were conducted among in adults aged 40 to 70 years, provided sufficient data for calculating ORs or relative risk with a 95% CI, were published as original articles written in English or other languages, and have been published until December 2017 will be included. Study selection, data collection, quality assessment, and statistical syntheses will be conducted based on discussions among investigators. Ethics and dissemination: Ethics approval was not required for this study because it was based on published studies. The results and findings of this study will be submitted and published in a scientific peer-reviewed journal. The findings from this study could be useful for assessing metabolic syndrome risk factors in stroke, and determining approaches for prevention of stroke in the future. Abstract : Supplemental Digital Content is available in the text